Case report of familial hypercholesterolemia with internal carotid neck swelling - Sudesh Kumar; Prajna Ray; Ranita Sahana (Journal of Family Medicine and Primary Care)
Familial hypercholesterolemia is a multi-gene disorder affecting 1 in 200-500 individual which is characterized by increased level of total cholesterol and low density lipoprotein (LDL) which deposit cholesterol reach protein leading to xanthomas, corneal arcus and prone to develop risk for atherosclerosis and coronary heart disease. 11 year female, born of consanguineous marriage attended with yellowish patches (Xanthelasma) bilaterally present over upper eyelid, buttock since 5-6 years. In family history younger girl along with both parents has Xanthelasma. In investigations, routine blood, urine and ECG& ECHO was normal except lipid profile of patient and sibling was abnormal. Child was treated with atorvastatin and dietary advice. In follow up after 3 month, child had complained of neck pain and swelling to left side. Then USG neck and Color Doppler showed reduced diastolic flow of left ICA and type two plaques and type 111 plaque in Rt common carotid artery. Anti-platelets was added and referred to cardiologist for coronary angiography which showed LAD – proximal mid distal diffuse plaque, LCX- proximal eccentric plaque. This case highlights the significance of conscious and proactive genetic screening for familial hypercholesterolemia especially in consanguineous marriage, to diagnose, treat and prevent mortality with premature coronary artery disease.